Changes and Disparities in Nature Access During the COVID-19 Pandemic - Byerly Flint, Hilary; Hammond Wagner, Courtney; Watson, Keri (Frontiers in Sustainable Cities, 2022)
Time in nature is associated with a range of physical and psychological benefits. These benefits tend to be unevenly distributed, with non-white and low-income communities often having lower access to nature than richer, more white neighborhoods. When the COVID-19 pandemic hit the United States in Spring 2020, changes in daily routines, restrictions on public nature access, and risk perceptions may have affected whether and how much people spent time in nature. We explore how nature access changed during the COVID-19 pandemic and how those changes were experienced by different demographic groups. We surveyed representative samples of California and New York residents (n = 2,036) in May and June of 2020 and examined differences in nature access and nature-related COVID restrictions and risks by gender, income and race. We find that, on average, the pandemic was associated with reductions in frequency of nature access and less time in nature for all respondents. However, these trends were greatest for women, people of color and people who are low-income. Moreover, the pandemic seems to have widened prior inequalities: low-income and non-white people accessed nature even less frequently and had fewer nature access options than they did prior to the pandemic. Given the disparities in broader pandemic impacts by gender, income, and race, these results further demonstrate the inequalities laid bare by COVID-19.